Encountering God Through Communal Feasting: A Critical Examination of the Minahasan Christian Thanksgiving Tradition from the Perspective of the Theology of Eating - Audriano Kalundang; Samuel Salainti (Proskuneo: Journal of Theology, 2026)
The tradition of Thanksgiving is a religious cultural heritage of the Minahasa Christian community that continues to thrive with communal meals as a central practice. Commensality not only plays an important role in building social relations and community cohesion, but also as a theological locus of encounter with God. This study discusses communal meals in Thanksgiving from the perspective of Norman Wirzba's theology of eating. Using a qualitative approach, this study employs literature review, analysis of relevant theological texts, and interviews with pastors and the Minahasa Christian community to gain an in-depth understanding of the practice of communal meals in Thanksgiving. The results of the study show that eating in Thanksgiving has three profound dimensions: First, communal eating functions as an act of faith that becomes a means of nurturing, fellowship, and hospitality. Second, communal eating shapes a new way of understanding food, fellow human beings, and God in the practice of Thanksgiving as a gift that must be appreciated. Third, communal eating becomes a space for social criticism and transformation to combat consumerism, social prestige, and food waste.